The reciprocal style and its impact on the development of some physical and motor abilities and the accuracy of correction of the Karbaji stability and movement of the team of the Department of Education Hit handball - Riyadh Ohmayed Mashaan; Nassr Khalid Abdulrazzaq; Othman Majeed Rasheed (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Abstract:The importance of the study lies in preparing an educational curriculum according tothe reciprocal method for some physical, motor, and skill-related abilities andidentifying the impact of the reciprocal method on developing some physical, motor,and skill-related abilities. The researchers used the experimental method due to itssuitability and the nature of the problem. The research sample comprised 14 studentsfrom the Hit Education Directorate's middle school team, divided into control andexperimental groups. Appropriate statistical methods were used to process the data.Based on the results obtained, the researchers concluded that the reciprocal methodoutperformed the direct method in the learning process regarding the research variables.One of the main recommendations is the necessity of using the reciprocal method in theskill-learning process.